2009
DOI: 10.1016/j.jstrokecerebrovasdis.2008.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Prior Antiplatelet Therapy, Platelet Infusion Therapy, and Outcome after Intracerebral Hemorrhage

Abstract: Background-Recent studies examining the effect of prior antiplatelet therapy (APT) on outcome in patients with spontaneous intracerebral hemorrhage (ICH) have shown conflicting results. The effect of platelet infusion therapy (PIT) on outcome in APT patients with ICH is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 16 publications
1
63
0
1
Order By: Relevance
“…We confirmed the results of previous studies [6,7] that demonstrated that platelet transfusion does not have a significant impact in preventing hematoma expansion, among patients taking aspirin. Of the patients that did not receive a transfusion, 29% of patients had an expansion, while 41% had an expansion following a transfusion.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We confirmed the results of previous studies [6,7] that demonstrated that platelet transfusion does not have a significant impact in preventing hematoma expansion, among patients taking aspirin. Of the patients that did not receive a transfusion, 29% of patients had an expansion, while 41% had an expansion following a transfusion.…”
Section: Discussionsupporting
confidence: 91%
“…The significant correlations [5,6] between aspirin use and poor outcome following ICH, probably due to hematoma expansion, suggest that minimizing hematoma growth should be a primary aim in the treatment of patients with aspirin associated ICH. Several studies reported that platelet transfusion for reversing antiplatelet therapy does not have a significant impact on the clinical outcome and does not prevent hematoma expansion [6,7]. The authors suggest that in the majority of these cases, hemorrhage expansion had already occurred before platelets were transfused.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 253 patients, aspirin use prior to ICH did not increase mortality, but mortality was increased in patients who took warfarin prior to ICH [66]. Another recent study of 368 ICH patients taking aspirin demonstrated increased risk of death (OR 2.4; 95% CI, 1.1-5.6), but platelet transfusion to reverse the antiplatelet effect did not prevent death (OR 1.2; 95% CI, 0.3-5.5) [67]. Naidech et al [68] showed in a prospective study that patients admitted with ICH with reduced platelet function at the time were associated with early ICH volume growth and with worse functional outcome.…”
Section: Antiplatelet Agentsmentioning
confidence: 98%
“…However, these were retrospective studies that did not specify the interval between admission and platelet administration or the dose used. (36) The morbidity due to intracranial bleeding should be weighed against the myocardial area at risk for thrombosis. If one opts for transfusion, the dose of 10 U of platelets is suggested after 300 mg of clopidogrel or 12.5 U after a loading dose of 600 mg. (37) Platelet function can also be improved with the use of desmopressin or recombinant activated factor VII (rFVIIa).…”
Section: Treatment Of Bleeding In Nste Acsmentioning
confidence: 99%